(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Social and economic equity, security, correspondence of status and openings, affirmation of the individual’s nobility make certain by the constitution of India for the whole resident in addition to other things. The social and economic hardship among Scheduled Castes had been generally basic during pre and post-Independence. The constitution of India is improved with a few arrangements for plan caste and timetable clans to shield and advance their social, social, instructive, economic and political interests to get them standard of the country. This paper addresses the socio-economic status of the timetable caste in Kangra region of Himachal Pradesh state (India). For achieving the targets two fifty instances of scheduled castes people were chosen. For recording their stories, Interview, Fuzzy Cognitive Mapping and subjective examination and translation were readied. The accounts were recorded, prepared, dissected and organized to determine significant topics and subthemes. The outcome dependent on subjective examination uncovered that the Socio-Economic state of certain Respondents isn’t acceptable. It‟s extremely hard to them to give great quality instruction to their youngsters. The majority of the families were rely on farming, yet because of some different issues the yield of agro items was bad. Greater part of respondents remained in sami kucha house. A large portion of respondent have power, water association and lavatory office. MGNREGA was the solitary rustic work program in the town MGNREGA was the lone country business program in the town, which resident known. Furthermore, a considerable lot of them took the advantage of this plan. Some of respondents take obligation from the banks for the instruction reason, wellbeing reason and some other reason. All respondents have cell phone office yet the least (vehicle) office. The majority of kids are concentrated in tuition based school inside town. A large portion of individuals have less mindfulness about the Govt. plans and program for the instruction advancement. All practically every house hold has the domesticated animals like cow, bison, sheep, goat and so forth Be that as it may, the greater part of them they don’t use them for the business reason. They use for their own motivation. Endowment framework wins in the general public and it is on request. Yet the greater part of respondent not scared of giving settlement. Caste framework exists in the general public. Because of MNREGA the monetary state of the SC ladies improved. By this the job of female likewise expanded in family dynamic and are additionally helped the kids and different individuals from family in their monetary prerequisites. The degree of certainty is likewise expanded. The social and economic status of scheduled caste individuals improved in pressure of before time. This is because of the schooling improvement and furthermore due the booking to the scheduled caste individuals in numerous areas.